PENGARUH PEMAHAMAN PERPAJAKAN DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK UMKM DI KOTA PEKANBARU - Kalsum, Ummi; Haryana, Gani; ', Gusnardi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The purpose of this study was to analyze the influence of tax knowledge, awareness of taxpayer on taxpayer compliance SMEs in Pekanbaru. The population in this study is the individual SMEs with turnover under $ 4.8 billion per year are 4.369 respondents. The sample is determined by area probability sample with 100 SMEs. Methods of data collection using the questionnaire. Analysis of the data used in this study is multiple linear regression analysis. The result showed that partial variable tax knowledge and awareness of taxpayer had effect on tax compliance Analysis of the factors examined in the study showed that the variables are the dominant influence on tax compliance is a variable awareness of taxpayer.Keywords: tax comprehension awareness of taxpayer, and tax compliance